Care(ful) relationships: Supporting children in secure care. Issue 3 (6th December 2020) - Ellis, Katie; Curtis, Penny
Abstract: Secure children's homes are used to accommodate children aged 10–16 under two main categories; while half are sentenced after committing a serious offence, the other half are placed because there are serious concerns around their safety in the community. Secure children's homes are prized within the secure estate, and they administer complex therapeutic support to 'the most vulnerable' young people, however little is known about the experiences of those employed to work in such spaces. This paper shares findings from PhD research conducted in one secure children's home over 1 year. Data presented are drawn from sensitive ethnographic fieldwork and in‐depth interviews with residential staff and residents in the home. Although young people's views are important, we concentrate here on the perspectives of residential staff to share their reflections of delivering 'care' and the strategies used to manage successful relationships within a secure setting. We conclude that residential staff tread a fine line between creating emotional closeness while maintaining physical distance and that they are sometimes unable to return the intensity of feeling that residents' direct towards them. We recommend that all residential staff receive regular and detailed supervision to provide opportunity to request support when necessary.